FEATURES OF PROTECTION OF CIVIL RIGHTS AND INTERESTS BY A NOTARY - Жмур, Наталія Володимирівна; Тодчук, Владислав Вікторович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the article examines the features and procedure for the protection of civil rights by a notary. Analyzed the views of scientists on the concept and essence of ways to protect civil rights. Research methods: philosophical and ideological, general scientific and special methods were used in the work. Results: the concept and essence of the protection of civil rights is determined. Kinds of way to protect civil rights. It was concluded: that free legal assistance is legal assistance, guaranteed by the state and fully or partially provided at the expense of the State Budget of Ukraine, local budgets and other sources and aimed at ensuring the realization of human and civil rights and freedoms, protection of these rights and freedoms, their recovery in case of violation. Discussion: of the role and place of protection of civil rights by a notary in the system of protection of civil rights. A notary intended to create appropriate conditions for the effective implementation of the rules of law by individuals and legal entities, protect their subjective rights and legitimate interests by providing public trust acts, and documents of greater probative force. We believe that the institute of notaries is a basic institution that protects civil rights and interests and has proved its reliability and legitimacy over a long period of time. Therefore, we join the position of those researchers who offer balanced approaches to the reform of the notaries, especially with regard to the transfer of some of its powers to professionally untrained professionals. We support those changes that are aimed at the development of the institute of notariate and its improvement.